Cross-Modal Attention Fusion of Radiomic Lung Nodule Features and Transcriptomic Phase-Separation Signatures for Explainable Cancer Risk Stratification - Arjun D. Shah; Pierre D. Kregory; Kasper Butler; Massimo Taylor (International Journal of Clinical and Translational Medicine, 2026)
Precision oncology demands risk stratification frameworks that synthesize heterogeneous biological evidence into actionable and interpretable predictions. This paper presents a system-level architecture for cross-modal attention fusion that integrates radiomic features extracted from lung nodule imaging with transcriptomic signatures shaped by biomolecular phase separation, aiming to deliver explainable cancer risk stratification. The work does not propose a single novel model; rather, it offers a sustained examination of the structural, governance, infrastructure, and policy dimensions associated with deploying such a cross-modal system in real clinical contexts. We argue that contemporary multimodal fusion methods, while powerful, often obscure the reasoning behind predictive outcomes, creating barriers to clinical trust, regulatory approval, and equitable deployment. By centering attention mechanisms that explicitly decouple modality-specific feature extraction from cross-modal interaction, the architecture promotes transparency through interpretable attention pathways. We discuss how radiomic features, long established for noninvasive tumor phenotyping, can be enriched by dual-attention segmentation networks, and how transcriptomic phase-separation signatures, which reveal condensate-driven gene regulation, provide a dynamic molecular complement. The paper critically examines trade-offs between predictive performance and explainability, explores infrastructure requirements for ingesting and aligning radiology and sequencing data at scale, and addresses fairness, robustness, and governance challenges that arise when such systems are embedded in clinical decision support. Throughout, the discussion emphasizes systemic resilience, policy alignment with evolving medical AI regulation, and sustainability of cross-institutional data collaborations. By treating the fusion pipeline as a socio-technical infrastructure, we provide a forward-looking perspective that connects attention-driven representation learning with the broader imperatives of responsible translation in oncology.